Dose tapering and discontinuation of biological therapy in rheumatoid arthritis patients in routine care – 2-year outcomes and predictors. (28th August 2018) - Brahe, Cecilie Heegaard; Krabbe, Simon; Østergaard, Mikkel; Ørnbjerg, Lykke; Glinatsi, Daniel; Røgind, Henrik; Jensen, Hanne S; Hansen, Annette; Nørregaard, Jesper; Jacobsen, Søren; Terslev, Lene; Huynh, Tuan K; et al.
Abstract: Objectives: A cohort of routine care RA patients in sustained remission had biological DMARD (bDMARDs) tapered according to a treatment guideline. We studied: the proportion of patients whose bDMARD could be successfully tapered or discontinued; unwanted consequences of tapering/discontinuation; and potential baseline predictors of successful tapering and discontinuation. Methods: One-hundred-and-forty-three patients (91% receiving TNF inhibitor and 9% a non-TNF inhibitor) with sustained disease activity score (DAS28-CRP)⩽2.6 and no radiographic progression the previous year were included. bDMARD was reduced to two-thirds of standard dose at baseline, half after 16 weeks, and discontinued after 32 weeks. Patients who flared (defined as either DAS28-CRP ⩾ 2.6 and ΔDAS28-CRP ⩾ 1.2 from baseline, or erosive progression on X-ray and/or MRI) stopped tapering and were escalated to the previous dose level. Results: One-hundred-and-forty-one patients completed 2-year follow-up. At 2 years, 87 patients (62%) had successfully tapered bDMARDs, with 26 (18%) receiving two-thirds of standard dose, 39 (28%) half dose and 22 (16%) having discontinued; and 54 patients (38%) were receiving full dose. ΔDAS28-CRP0-2yrs was 0.1((−0.2)-0.4) (median (interquartile range)) and mean ΔTotal-Sharp-Score0-2yrs was 0.01(1.15)(mean(s .d .)). Radiographic progression was observed in nine patients (7%). Successful tapering was independently predicted by: ⩽1 previous bDMARD, male gender, low baseline MRI combined inflammation score or combined damage score. Negative IgM-RF predicted successful discontinuation. Conclusion: By implementing a clinical guideline, 62% of RA patients in sustained remission in routine care were successfully tapered, including 16% successfully discontinued at 2 years. Radiographic progression was rare. Maximum one bDMARDs, male gender, and low baseline MRI combined inflammation and combined damage scores were independent predictors for successful tapering.